CONCEPTUAL FOUNDATIONS OF ANALYSIS REGIONAL POLICY: A POLITICAL DIMENSION - Голуб’як, Н. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article there has been researched the essence, characteristic features and peculiarities of development of directions and theories of a regional policy. The author shows and analyzes the representatives of different schools at development of regional theories. The role of regional development is exposed in modern political processes. The author proposed approach to building systemic organization of regional development, and developed theoretical approaches to defining paradigms of functioning of regional policy.